Neurobehavioral effects of long‐term maternal fructose intake in rat offspring. Issue 69 (9th July 2018) - Erbas, Oytun; Erdogan, Mümin Alper; Khalilnezhad, Asghar; Gürkan, Fulya Tuzcu; Yiğittürk, Gürkan; Meral, Ayfer; Taskiran, Dilek
Abstract: Background: Previous studies have indicated an association between maternal metabolic conditions and general developmental disturbances of the offspring. Objective: We aimed to investigate the influence of long‐term maternal fructose intake during gestation and lactation on neurobehavioral development of rat offspring. Methods: Twelve female Sprague Dawley rats were received either 30% fructose enriched water (n = 6) or regular tap water (control, n = 6) for 12 weeks. Then, control and fructose‐received females were caged with a fertile male, and received 30% fructose and regular chow throughout pregnancy, delivery and until offspring's weaning. On P21, forty littermates (10 male control, 10 female control, 10 male fructose and 10 female fructose) were separated and housed with ad libitum access to standard food and tap water. Following behavioral evaluations at P50, brain levels of TNF‐α, neuregulin 1 (NRG1), glutamic acid decarboxylase 67 (GAD67), nerve growth factor (NGF), insulin‐like growth factor 1 (IGF‐1), and 5‐hydroxyindoleacetic acid (5‐HIAA) were measured. Histologically, hippocampal neuronal density and GFAP expression were assessed. Results: Analysis of the behavioral tests (three‐chamber social test, open field test, passive avoidance learning test and stereotypy test) revealed significant differences among the groups. Histologically, hippocampal CA1 and CA3 regions displayed significant alterations such as gliosis and neuronal cell death in fructose‐exposed groups compare to controls. Biochemical measurements of the brain levels of TNF‐α and neurodevelopmental markers showed significant differences between controls and fructose‐exposed groups. Conclusion: These results suggest a possible link between the chronic maternal metabolic stress, such as long‐term fructose intake, and neurodevelopmental disturbances in the offspring.